Advancing culture of living with landslides. Volume 1, - Sassa, Kyoji; Mikoš, Matjaž; Yin, Yueping (SpringerOpen, 2017)
This book is open access under a CC BY 4.0 license. This volume contains peer-reviewed papers from the Fourth World Landslide Forum organized by the International Consortium on Landslides (ICL), the Global Promotion Committee of the International Programme on Landslides (IPL), University of Ljubljana (UL) and Geological Survey of Slovenia in Ljubljana, Slovenia from May 29 to June 2, 2017. The complete collection of papers from the Forum is published in five full-color volumes. Thisfirst volume contains the following: - Three forum lectures - Background and Content of the Sendai Partnerships 2015-2025 - Contribution from the signatory organizations of the Sendai Partnerships - Landslide Dynamics: ISDR-ICL Landslide Interactive Teaching Tools (LIT T) - Progress of the World Report on Landslides (WRL) - International Programme on Landslides (IPL): Objects, History and List of WCoE/IPL projects - UNESCO-KU-ICL UNITIWIN Network supporting IPL - Landslides: Journal of International Consortium on Landslides - International Programme on Landslides (IPL): WCoEs and IPL Projects - Landslides and Society Prof. Kyoji Sassa is the Founding President of the International Consortium on Landslides (ICL). He is Executive Director of ICL and the Editor-in-Chief of International Journal Landslides since its foundation in 2004. Prof. Matjaž Mikoš is the Forum Chair of the Fourth World Landslide Forum. He is the Vice President of International Consortium on Landslides and President of the Slovenian National Platform for Disaster Risk Reduction. Prof. Yueping Yin is the President of the International Consortium on Landslides and the Chairman of the Committee of Geo-Hazards Prevention of China, and the Chief Geologist of Geo-Hazard Emergency Technology, Ministry of Land and Resources, P.R. China. IPL (International Programme on Landslides) is a programme of the ICL. The programme is managed by the IPL Global Promotion Committee including ICL and ICL supporting organizations, UNESCO, WMO, FAO, UNISDR, UNU, ICSU, WFEO, IUGS and IUGG. The IPL contributes to the United Nations International Strategy for Disaster Reduction and the ISDR-ICL Sendai Partnerships 2015-2025.
Keywords: Landslides.; elektronické knihy; electronic books